Role of Multimedia in Depicting the Social Issues of People with ID - Bolatovna, Alimzhanova Aikerim; Erkinuly, Issabek Nurdaulet; Serikalievna, Zhaxylykbaeva Rimma; Khamzauly, Kamzin Kaken; Dauren, Mukhamedzhanov (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
This research paper discusses the role of multimedia journalism in depicting the social issues of people with intellectual disabilities (ID) and how modern multimedia supports them. This study aimed to examine how multimedia supports people with intellectual disabilities and how it helps people cope with this problem. The survey covered the year 2017. The purpose of this qualitative study was to produce an overview of topics and practical recommendations that have been presented for multimedia journalism students to cooperate with the problem of people with ID, how to conduct assistance and highlight their issues in media. The topic was widely studied, and the outline was made by focusing on the practical implications of research articles. The implications for practice and research are presented based on the findings of this study